2022
DOI: 10.15294/jpii.v11i3.38275
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Flipped Classroom-Based Project Assessment on Concept Understanding and Critical Thinking Skills in Physics Learning

Abstract: This study aims to analyze the influence of flipped classroom-based project assessment on critical thinking skills and physics learning outcomes. This quantitative research has a post-test-only non-equivalent control group design. The population is distributed into two classes. The data are collected using questionnaires and tests and analyzed using descriptive statistics and Manova. The results indicate differences between critical thinking skills and physics learning outcomes between students who learned wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…Various previous studies have shown the same results, namely that the application of learning models can improve critical thinking skills, among other things Android-based media in Androwebic and E-Bokartumban (Isnaeni, Sujatmiko, and Pujiasih, 2021), reflective inquiry learning (Verawati et al, 2021), Problem-based interactive physics e-modules (Sujanem and Suwindra 2023), Learning Strategy "Students as Researchers" (Daryanes et al, 2023). Flipped classroom learning based on disaster map visualization (Astawa et al, 2022) and flipped Classroom-Based Project Assessment (Rapi et al, 2022) influence critical thinking skills.…”
Section: Discussionmentioning
confidence: 67%
“…Various previous studies have shown the same results, namely that the application of learning models can improve critical thinking skills, among other things Android-based media in Androwebic and E-Bokartumban (Isnaeni, Sujatmiko, and Pujiasih, 2021), reflective inquiry learning (Verawati et al, 2021), Problem-based interactive physics e-modules (Sujanem and Suwindra 2023), Learning Strategy "Students as Researchers" (Daryanes et al, 2023). Flipped classroom learning based on disaster map visualization (Astawa et al, 2022) and flipped Classroom-Based Project Assessment (Rapi et al, 2022) influence critical thinking skills.…”
Section: Discussionmentioning
confidence: 67%
“…In other words, the use of CPS-based emodules does not significantly influence the improvement of students' digital literacy. Nevertheless, CPS has developed responses to enhance students' thinking processes (Rubenstein, 2019) in organizing creative ideas (Beda, 2020;Rahayu, 2022). CPS-based e-modules that allow students to interact with interactive text or images presented are not sufficient to enhance students' digital literacy.…”
Section: Discussionmentioning
confidence: 99%
“…The subject of Physics is highly suitable for applying the CPS model. Physics is the most fundamental science with complexities identical to problem-solving (Puspitasari, 2021;Rahayu, 2022). Physics learning often involves contextual problems (Satriawan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Today, various platforms that are widely used by schools and universities have been exploited in order to promote proper interaction among the educational community, and thus students become more responsible towards their obligations. Google Classroom, Blackboard, Moodle, and other similar platforms are nowadays commonly used [28], [29].…”
Section: Flipped Classroommentioning
confidence: 99%